2016
DOI: 10.1037/xlm0000176
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the processing of written sarcasm and metaphor: Evidence from eye movements.

Abstract: The present study examined individual differences in the processing of different forms of figurative language. Sixty participants read sarcastic, metaphorical, and literal sentences embedded in story contexts while their eye movements were recorded, and responded to a text memory and an inference question after each story. Individual differences in working memory capacity (WMC), need for cognition (NFC), and cognitive-affective processing were measured. The results showed that the processing of metaphors was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
112
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(133 citation statements)
references
References 58 publications
(126 reference statements)
17
112
2
2
Order By: Relevance
“…According to this framework, readerrelated factorssuch as how frequently a person uses sarcasm influence the likelihood that different interpretations (literal, sarcasm, or white lie) are active in the reader's mind. In line with this, recent eye-tracking studies have suggested that individual differences in working memory capacity (WMC) and the ability to process emotional information impact the likelihood of re-reading sarcastic texts (Kaakinen et al, 2014;Olkoniemi et al, 2016;Olkoniemi et al, in press).…”
Section: Individual Differences In the Processing Of Sarcasmmentioning
confidence: 89%
See 3 more Smart Citations
“…According to this framework, readerrelated factorssuch as how frequently a person uses sarcasm influence the likelihood that different interpretations (literal, sarcasm, or white lie) are active in the reader's mind. In line with this, recent eye-tracking studies have suggested that individual differences in working memory capacity (WMC) and the ability to process emotional information impact the likelihood of re-reading sarcastic texts (Kaakinen et al, 2014;Olkoniemi et al, 2016;Olkoniemi et al, in press).…”
Section: Individual Differences In the Processing Of Sarcasmmentioning
confidence: 89%
“…In this type of setting, a reader must search for an alternative interpretation of the utterance and incorporate this into the memory representation of the text. In support of these theoretical views, recent eye-tracking studies have shown that written sarcastic utterances take more time to process and are harder to comprehend than their literal counterparts (Au-Yeung, Kaakinen, Liversedge, & Benson, 2015;Filik, Leuthold, Wallington, & Page, 2014;Filik & Moxey, 2010;Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014;Olkoniemi, Ranta, & Kaakinen, 2016;Olkoniemi, Strömberg, & Kaakinen, in press;Turcan & Filik, 2016).…”
Section: Resolving the Meaning Of Sarcastic Utterancesmentioning
confidence: 93%
See 2 more Smart Citations
“…More recently, a few studies have applied online measures, such as eye‐tracking and event‐related brain potentials (ERPs), to investigate how readers keep track of temporal and emotional shifts in stories, and have demonstrated that readers are sensitive to mismatches between a character's expected and described emotional states [Carminati & Knoeferle, 2013, 2016; Komeda & Kusumi, 2006; Leuthold, Filik, Murphy, & Mackenzie, 2012; Munster, Carminati, & Knoeferle, 2014; Ralph‐Nearman & Filik, 2018; Rinck & Bower, 2000; Vega, 1996; Zwaan, 1996]. Moreover, some researchers have examined the online processes underlying sarcasm comprehension using eye‐tracking [e.g., Au‐Yeung, Kaakinen, Liversedge, & Benson, 2015; Deliens, Antoniou, Clin, Ostashchenko, & Kissine, 2018; Filik, Howman, Ralph‐Nearman, & Giora, 2018; Filik, Leuthold, Wallington, & Page, 2014; Filik & Moxey, 2010; Kaakinen, Olkoniemi, Kinnari, & Hyönä, 2014; Olkoniemi, Ranta, & Kaakinen, 2016; Olkoniemi, Johander, & Kaakinen, 2019; Olkoniemi, Strömberg, & Kaakinen, 2019; Țurcan & Filik, 2016, 2017]. These studies generally find that comprehending irony incurs higher processing costs than comprehending literal language, suggesting that the salient meaning (i.e., the most familiar, frequent, and conventional meaning) is activated by default and must be overridden to interpret ironic statements, irrespective of how biasing the context is [Giora, 1997, 2003].…”
Section: Introductionmentioning
confidence: 99%